Digital Safety Management Systems and Green Finance for MSMEs Financial Sustainability: Evidence from ESG-Based Risk Management - Etty Harya Ningsi; Dina Hastalona (Invoice : Jurnal Ilmu Akuntansi, 2026)
The rapid advancement of digital transformation and the growing global emphasis on sustainability have placed Micro, Small, and Medium Enterprises (MSMEs), particularly in emerging economies such as Indonesia, under increasing pressure to enhance financial resilience while aligning with Environmental, Social, and Governance (ESG) standards. In the context of MSMEs in Medan City, North Sumatra, digitalization offers opportunities for efficiency and market expansion but also introduces challenges, including cyber risks, weak digital security governance, and limited access to green financing. These constraints may hinder long-term financial sustainability without integrated governance and effective risk management. This study examines the influence of Digital Safety Management Systems and Green Finance on MSMEs’ Financial Sustainability, with ESG-Based Budgeting and Risk Management as mediating variables. A quantitative explanatory approach was employed using purposive sampling of 230 MSMEs with digital system adoption and access to formal financing. Data collected from December 2025 to February 2026 were analyzed using SEM-PLS. The results show that Digital Safety Management Systems and Green Finance significantly enhance Financial Sustainability both directly and indirectly. The mediation analysis indicates partial mediation, with Risk Management as the most influential mechanism. This study contributes by integrating digital safety governance and green finance within an ESG-based risk management framework, offering a novel perspective that bridges fintech risk management and sustainability accounting in MSMEs. The findings provide practical insights for policymakers in developing countries to strengthen MSME sustainability.